Hunting evil : the Nazi War criminals who escaped and the quest to bring them to justice - Walters, Guy 1971- (Broadway Books, 2009)
At the end of World War II, an estimated 30,000 Nazi war criminals fled from justice, including some of the highest ranking members of the Nazi Party. In this exhaustively researched work of history and investigative reporting, journalist Guy Walters gives a comprehensive account of how the most notorious Nazi war criminals escaped justice, how they were pursued, captured or able to remain free until their natural deaths, and how they were assisted on the run by "helpers" ranging from a Vatican bishop to a British camel doctor, and even members of Western intelligence services. Based on all new interviews with Nazi hunters and former Nazis and intelligence agents, travels along the actual escape routes, and archival research in Germany, Britain, the United States, Austria, and Italy, this book authoritatively debunks much of what has previously been understood about Nazis and Nazi hunters in the postwar era.--From publisher description